2010
DOI: 10.1159/000279305
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and the Accumulation of Iron in the Basal Ganglia: Quantitative Assessment of Brain Iron Using MRI T<sub>2</sub> Relaxometry

Abstract: The aim of this work was to quantify the accumulation of iron in the basal ganglia in multiple sclerosis (MS) patients and in a control group, and to investigate the relationship between iron accumulation and other parameters assessed in MS, i.e. lesion load (LL) and brain parenchymal fraction (BPF). Magnetic resonance imaging T2 relaxometry was used for the measurement. 970 patients with clinically definite MS and 117 controls were examined. Patients were divided into three subgroups according to L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 61 publications
3
41
0
1
Order By: Relevance
“…24,25 More recently, MR imaging techniques, such as T2 relaxometry, [17][18][19] T2 hypointensity, [14][15][16]30,39 magnetic field correlation, 20 and SWI [21][22][23]40 have been used to quantify and visualize iron deposition in vivo. Looking at changes in T2 intensity is a relatively straightforward method of evaluating iron content, because increased levels of iron result in reduced T2 relaxation time, leading to hypointensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 More recently, MR imaging techniques, such as T2 relaxometry, [17][18][19] T2 hypointensity, [14][15][16]30,39 magnetic field correlation, 20 and SWI [21][22][23]40 have been used to quantify and visualize iron deposition in vivo. Looking at changes in T2 intensity is a relatively straightforward method of evaluating iron content, because increased levels of iron result in reduced T2 relaxation time, leading to hypointensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…1 GM damage is most extensive in patients with progressive MS, 2 but is already present in those with CIS [3][4][5][6][7][8][9][10] and can predict conversion to clinically definite MS. [11][12][13] Most authors investigating iron deposition in MS have used imaging techniques such as T2 hypointensity, [14][15][16] relaxometry, [17][18][19] magnetic field correlation, 20 and SWI. [21][22][23] Accumulation of iron in the SDGM has also been observed histologically in MS, 24,25 and iron deposition has been detected in the same SDGM structures where the volume loss also occurred.…”
mentioning
confidence: 99%
“…Abnormal iron deposits were detected particularly in the deep gray matter (DGM)-that is, in the putamen, caudate nucleus (CN), and globus pallidus (GP) with iron-sensitive MR imaging techniques such as R2* relaxometry, magnetic field correlation imaging, phase imaging, and quantitative susceptibility mapping (QSM). [1][2][3][4][5][6][7][8] Neuropathologic studies in MS confirmed increased iron content in both glial cells and neurons in DGM associated with degenerative changes, 9 while overall iron loss was observed in normal-appearing white matter. 10 An increase in iron concentration appears to be an early phenomenon, with the highest amounts of accumulation occurring during the transitions from clinically isolated syndrome to definite MS. 11 Currently, little information is available on the differences in iron content in various MS subtypes.…”
mentioning
confidence: 88%
“…Another study by Burgetova et al 20 by using T2 relaxometry showed that iron does increase in the basal ganglia and the THA of patients with MS, but it showed an inverse correlation with lesion load. Zhang et al 21 also reported a correlation between T2 hypointensities (representing iron deposition) and the patients' disabilities in the RRMS group they studied.…”
mentioning
confidence: 96%